2010
DOI: 10.1007/s12032-010-9516-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of breast cancer patients with N3a (≥10 positive lymph nodes) disease: has it changed over years?

Abstract: It has been shown that breast cancer patients with N3a (10 positive lymph nodes) had a poor prognosis. We planned to investigate the clinical outcome BC patients who presented with N3a disease and had no evidence of systemic metastasis at the time of diagnosis. We made a retrospective chart review of breast cancer patients who had ≥10 positive lymph nodes and received adjuvant systemic therapy in Marmara University Hospital between 1998 and 2008. We recorded clinical, pathologic and treatment characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 29 publications
3
17
2
Order By: Relevance
“…There are some controversies on the prognostic value of T stage in pN3a disease. Some authors have reported that there are prognostically different subgroups in pN3a disease by T stage [8,9], while other studies did not show the prognostic value of T stage [5,10,13,14]. In our study, pN3a patients with T4 tumors had significantly worse DFS and OS compared to those with a T1-3 tumor in univariate analysis, but failed to show statistical significance in the multivariate analysis.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…There are some controversies on the prognostic value of T stage in pN3a disease. Some authors have reported that there are prognostically different subgroups in pN3a disease by T stage [8,9], while other studies did not show the prognostic value of T stage [5,10,13,14]. In our study, pN3a patients with T4 tumors had significantly worse DFS and OS compared to those with a T1-3 tumor in univariate analysis, but failed to show statistical significance in the multivariate analysis.…”
Section: Discussioncontrasting
confidence: 82%
“…Another study reported that the 5-year survival rates for patients with 11-15, 16-20, and 21 or more positive nodes were 55, 49 and 38%, respectively [16]. In addition, many studies have suggested that the number of positive lymph nodes is the strongest prognostic factor in patients with pN3a disease [5,10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study produced long-term DFS (5-year: 59.3%; *Event-free survival; ** Estimated 10-year: 37.9%) and OS (5-year: 66.6%; 10-year: 43.9%) similar to other cohorts analyzed over the past decade, which produced a 5-year DFS ranging from 42.9-66% and a 5-year OS ranging from 57-81% (Table 5, Schmoor et al, 2001;Basaran et al, 2011;Lee et al, 2011). This is in stark contrast to earlier cohorts that saw 5-and 10-year OS survival rates of 39% and 24%, respectively (Buzdar et al, 1992;Walker et al, 1995).…”
Section: Discussionsupporting
confidence: 59%
“…These patients constitute only a small subset of the study population in large-scale prospective BC trials [6]. Retrospective studies usually have nonhomogeneous patient populations [7,8,9,10]. A recent study noted that, unlike early recurrence, the tumor biology may have a more important role than the tumor load (positive lymph nodes) for late recurrence in ER-positive disease [11,12].…”
Section: Introductionmentioning
confidence: 99%